Kesantunan Berbahasa pada Kalangan Remaja di Keluarga Kota Medan Kecamatan Manna Kabupaten Bengkulu Selatan - Rezali, Riski Ahmad; Suryadi, Suryadi; Rahayu, Ngudining (Jurnal Korpus, 2025)
The purpose of this study was to describe politeness in language among teenagers in Kelurahan Kota Medan, Manna District, South Bengkulu Regency, namely the maxim of wisdom, the maxim of generosity, the maxim of praise, the maxim of humility, the maxim of opportunity, and the maxim of agreement. The data collection techniques used in this study include observation techniques, then recording techniques and note-taking techniques. The subjects of this study were teenagers in Kelurahan Kota Medan, Manna District, South Bengkulu Regency. The data analysis method is descriptive qualitative. The results of the study show that teenagers in the Medan City Subdistrict, Manna District, South Bengkulu Regency apply politeness in language with the following six maxims: (1) the maxim of wisdom spoken by teenagers with teenagers, (2) the maxim of generosity spoken by teenagers with teenagers and teenagers with parents, (3) the maxim of praise spoken by teenagers with teenagers, (4) the maxim of humility spoken by teenagers with teenagers, (5) the maxim of agreement spoken by teenagers with teenagers with teenagers and teenagers with parents, and (6) the maxim of sympathy spoken by teenagers with teenagers.